Determinants of providing smoking cessation care in five groups of healthcare professionals: A cross-sectional comparison. Issue 6 (June 2019) - Meijer, Eline; van der Kleij, Rianne; Segaar, Dewi; Chavannes, Niels
Highlights: Implementation of smoking cessation care differs between healthcare professions. Main barriers to guideline implementation are lack of training and lack of time. Training is associated with better implementation of smoking cessation care. Regression tree analyses showed that determinants interact in explaining outcomes. Efforts to improve implementation should be targeted tailored to each profession. Abstract: Objective To investigate implementation of a tobacco dependence treatment guideline among five groups of healthcare professionals. Methods Data collected in The Netherlands (2016–2017) were compared among gynaecologists (N = 49), midwives (N = 68), respiratory nurses (N = 72), practice nurses (N = 84) and paediatricians (N = 38). Intentions to use the guideline, satisfaction with own implementation, and dosage delivered of quit-advice and assisting in quitting were predicted using linear regression analyses and regression tree analyses. Results Implementation of smoking cessation care (SCC) and barriers differed between the groups, with nurses reporting better implementation and fewer barriers. Main barriers were lacking training (gynecologists, pediatricians) and time (midwives). Regression tree analyses showed that self-efficacy and training interacted; participants with weaker self-efficacy provided more quit advice if they had participated in SCC training. Training was positively related to intentions to use the guideline, satisfaction, providing quit-advice, and assisting smokers in quitting. Conclusion Implementation of SCC is suboptimal, such that patients who smoke do not receive the highest quality of care. Profession and training in SCC are important determinants of implementation of SCC. Practice implications Efforts to improve implementation should be targeted at profession. Training is indicated, and may focus on skills for nurses, and knowledge for gynecologists, midwives and pediatricians.